2011
DOI: 10.1159/000329801
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Balancing Tolerance and Immunity in the Liver

Abstract: The liver has a pivotal role in glucose, lipid and protein metabolism as well as in removal of toxins and waste products. A unique microanatomy and a network of resident scavenger cell populations specialized in endocytic uptake of antigens and macromolecules cooperatively mediate these salient hepatic functions together with parenchymal hepatocytes. Antigens taken up by hepatic scavenger cell populations, such as Kupffer cells, hepatic dendritic cells, stellate cells and liver sinusoidal endothelial cells (LS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 93 publications
0
38
0
Order By: Relevance
“…In our liver samples no signs of necrotic damage or morphologically evident inflammation were present (as expected in the general donor population), and thus the presence of i-proteasomes even in liver of young donors free from inflammatory infiltrates indicates that a basal level of proinflammatory ''tone'' can be considered physiological, likely sustained by the continuous exposure to antigenic stimuli coming from the gut microbiota via the portal vein. In fact hepatocytes express a number of pattern recognition receptors (PRR), such as TLR3, RIG-I and MDA5, that can sustain the production of inflammatory cytokines (Bö ttcher et al, 2011;Broering et al, 2001). At the same time, a permanent activation of intracellular signalling pathways can be envisaged (Ebstein et al, 2012;Grimm et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In our liver samples no signs of necrotic damage or morphologically evident inflammation were present (as expected in the general donor population), and thus the presence of i-proteasomes even in liver of young donors free from inflammatory infiltrates indicates that a basal level of proinflammatory ''tone'' can be considered physiological, likely sustained by the continuous exposure to antigenic stimuli coming from the gut microbiota via the portal vein. In fact hepatocytes express a number of pattern recognition receptors (PRR), such as TLR3, RIG-I and MDA5, that can sustain the production of inflammatory cytokines (Bö ttcher et al, 2011;Broering et al, 2001). At the same time, a permanent activation of intracellular signalling pathways can be envisaged (Ebstein et al, 2012;Grimm et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it was shown that IL-6 might completely inhibit the generation of Treg cells induced by TGF-β [51], as well as that the administration of TGF-β1 in vivo might improve the clinical course of EAE, similarly as polyphenolic phytochemical curcumin, which after the downregulation of the expression of IL-6, IL-21, ROR t signaling and inhibition of STAT3 phosphorylation inhibited the differentiation and development of Th17 cells [53]. It should be also emphasized that TGF-β signaling might affect the processes of unique antigen presentation by local adipocyte progenitor cell populations in the liver, such as dendritic cells, Kupffer cells, and liver sinusoidal endothelial cells that result in induction of the antigen-specific peripheral tolerance rather than in induction of T cell immunity [47,54,55]. Our data showing the greater activation of NFκB in Kupffer cells of AO rats seem to point in this direction (fig.…”
Section: Discussionmentioning
confidence: 99%
“…19 For a more detailed account of the immunological properties of the liver, several comprehensive reviews have been previously published. 17,18,[20][21][22][23][24][25][26][27][28] DETERMINANTS OF ACUTE AND CHRONIC HCV INFECTION Acute infections are typically asymptomatic, therefore studies on immunity to HCV infection have been for the large part limited to chronically infected patients or immune chimpanzees. 13 The outcome of acute infection is generally configured within the initial 6 months and ultimately depends on the magnitude, breadth and specificity of the adaptive immune response.…”
Section: Foxp3mentioning
confidence: 99%